Which organisational context factors help women to obtain and retain leadership positions in the 21st century? A systematic review and research agenda for human resource management - Lioba A. Gierke; Sofia Schlamp; Fabiola H. Gerpott (Human Resource Management Journal, 2024)
Obtaining and retaining women in leadership positions is an ongoing challenge for scholars and practitioners in Human Resource Management (HRM). Research on the role of organisational context factors in supporting women who either are already in leadership roles or aspire to obtain them is fragmented and spread across multiple disciplines. In this systematic literature review, we identified 87 articles related to organisational context factors and female leadership. We mapped these articles onto the stages of the employee lifecycle: (1) Recruitment and Selection, (2) Learning and Development, (3) Performance Appraisal, and (4) Reward and Retention. Additionally, we introduced the category (5) Organisational Setting to encompass overarching context factors such as industry. For each article, we assessed the underlying assumptions concerning the gender-neutrality or gender-sensitivity in the practical implications. Our analysis revealed that some stages of the employee lifecycle received more attention than others and that the derived practical implications often go far beyond what can be concluded based on the study findings. We discuss theoretical implications and outline future research opportunities, such as the potential for HRM scholars to integrate an intersectionality lens into research along the employee lifecycle. We end with practical implications for HRM practitioners who wish to implement evidence-based insights from our review.
Keywords: 650; gender; leadership; organisational context factor; systematic literature review; women